Mangrove oyster (Crassostrea rhizophorae) (Guilding, 1928) farming areas as artificial reefs for fish: A case study in the State of Ceará, Brazil (Brazilian Journal of Oceanography, 2006)
A type of platform, known as a table, is now being used for mangrove oyster farming. In Fortim, Ceará, Brazil, this activity was begun in June 2000 and covers an area of 50 m² overlying a sand-clay substrate. The present study has the following main objectives: to identify and catalogue the ichthyofauna colonizing the Crassostrea rhizophorae farming platforms; to evaluate ecological aspects, such as the possible correlation between the physical and chemical variables for water quality and the occurrence of the ichthyofauna; and to observe the differences in the fish species found during tidal variations. Specimens were identified and quantified using the linear-transect, visual census methodology. The ichthyofauna observed comprised 3,030 individuals belonging to 28 species and 20 families. Of the 28 species found in the area studied, 14 were marine transients, 12 marine dependent, and only 2 permanent residents. A significant association was observed between the abundance of 11 species and the physical and chemical variables studied. Based on these results, it may be concluded that the platforms act as artificial reefs for the ichthyofauna, being colonized by at least 28 species, and providing protection from predators as well as a source of food and a reproductive substrate.